Bank Integration and the Market for Corporate Control: Evidence from Cross-State Acquisitions - John, Kose; Qi, Qianru; Wang, Jing (Management Science, 2020)
Using the staggered and reciprocal passage of interstate bank deregulation as an exogenous variation in the degree of bank integration, we investigate how and why bank integration influences the market for corporate control for nonfinancial firms. We posit that bank integration affects acquisitions either through reducing the information asymmetry between acquirers and targets or through increasing credit supply. Our evidence is more consistent with the former channel. Specifically, we document that (1) cross-state acquisitions are more likely to occur between reciprocally deregulated states, and (2) firms are more likely taken over by out-of-state acquirers after deregulation; this effect is stronger for a target who borrows from an out-of-state bank, whose local bank is acquired by an out-of-state bank, and who is informationally more opaque. Announcement returns for acquirers of out-of-state (particularly private) targets increase after deregulation, consistent with better identification of higher-valued targets by acquirers after deregulation. This paper was accepted by Tomasz Piskorski, finance.